EVALUASI UI/UX DARI APLIKASI IKMAS DENGAN MENGGUNAKAN METODE DESIGN THINKING DAN PENGUJIAN PENGGUNA - Syifa Nur Islami; Muhamad Dody Firmansyah (LPPM Universitas Abdurrab, 2024)
Pondok Pesantren Modern Islam Assalaam introduced the IKMAS application to modernize the alumni system with around 10,000 graduates. However, the total downloads of this app only reached just over 1 million user downloads on the Google Play Store. Some reviews highlighted the app's lack of attractiveness and neatness, which made it inconvenient, especially due to inadequate navigation. Evaluating the interface design (UI) of the IKMAS app is an effort to improve the app's performance and user experience (UX). This research aims to align the interface design (UI) with user needs based on user experience (UX). The evaluation was conducted using design thinking method, with usability testing using System Usability Scale (SUS) and Single Ease Question (SEQ). The average result of testing with SUS that is considered good is â‰¥ 68. Before the design improvement, the average SUS score was 65. After UI/UX improvement with design thinking method, the average SUS value increased to 81.5 and SEQ reached 95%.